Global longitudinal strain at 3 months after therapy can predict late cardiotoxicity in breast cancer - Zhiyue Liu; Mei Liu; Xiaorong Zhong; Yupei Qin; Ting Liang; Ting Luo; Xi Yan; Zhuoqin Tang; Xi Wang; Shichu Liang; Qian Li; Xiaomiao Ruan; et al. (Cancer Medicine, 2023)
Abstract Background Cancer therapy‐related cardiovascular toxicity (CTR‐CVT) is a major contributor to poor prognosis in breast cancer (BC) patients undergoing chemotherapy. Left ventricular global longitudinal strain (LV GLS) has predictive value for CTR‐CVT, while few researchers take into account late‐onset CTR‐CVT. This study sought to provide a guide for the prediction of late‐onset CTR‐CVT in primary BC over the 2 years follow‐up via strain and contrast‐enhanced echocardiography. Methods Anthracycline and anthracycline + targeted medication groups were created from 111 patients with stage I–III primary BC who were prospectively included. The left ventricular diastolic function, LV global long‐axis strain (GLS); left ventricular ejection fraction by contrast‐enhanced echocardiography (c‐LVEF), and electrocardiograms were collected at baseline, 3, 6, 12, and 24 months after the start of cancer treatment. The high‐sensitivity troponin‐T and NT‐pro BNP at baseline and 3 months after chemotherapy were measured. Results (1) LV GLS decreased in BC patients over time. (2) After 12 months' follow‐up, the LV GLS in the anthracycline+ targeted group was lower than in the anthracycline group. After 24 months' follow‐up, the GLS and c‐LVEF in the anthracycline + targeted group declined while the E/e’ increased. (3) Decreased LVEF (56%) and arrhythmia (38%) are the common causes of CTR‐CVT. Lower LVEF was a major factor in late‐onset CTR‐CVT. (4) Combination of LV GLS and c‐LVEF at 3 months were used as predictors for CTR‐CVT and exhibited a higher AUC than either one alone (AUC = 0.929, 95% CI: 0.863–0.970). LV GLS at 3 months can predict the late‐onset CTR‐CVT (AUC = 0.745, p < 0.001), and the cut‐off is 20.32%. Conclusions As time went on, the systolic and diastolic dysfunction of BC patients get worsened. The combination of LV GLS and c‐LVEF is better in the prediction of CTR‐CVT. Only the LV GLS at 3 months can predict the late‐onset CTR‐CVT.